Pengaruh Tingkat Pendapatan Individu Berdasarkan UMP Terhadap Tingkat Kebahagiaan di Provinsi DIY - Joshua Agung Nurcahyo; Hanif Rosyadah; Fitriana , Fitriana (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
A region's level of welfare and development can be measured using subjective and objective welfare. Subjective well-being measured by taking an individual approach and paying attention to individual subjective perceptions of life; one of the measurement indicators is happiness. In the Province of DIY, there is an interesting phenomenon although per capita income and UMP are relatively low, the level of happiness is high. Based on this phenomenon, further research is needed to determine whether individual income levels based on UMP affect individual happiness in DIY. Binary logistic regression modeling using IFLS 5 data shows that individuals with incomes above the UMP tend to be happier than those below the UMP. On the other hand, the people of DIY have cultural values that teach them to accept the reality of life in order to gain happiness with sincerity. The existence of this character makes people have confidence and optimism in any condition, so they feel happy. Based on the findings of the analysis and literature review, in general, the people of DIY have a level of happiness that is classified as happy. However, if there is an increase in income, the level of happiness also tends to increase to be happier. These findings suggest that increased income can be an essential factor in increasing individual happiness. However, efforts to increase happiness focus on more than just material aspects but also involve other aspects that affect life and well-being, such as culture and personal character.